Uncovering the origin of enhanced field emission properties of rGO-MnO(2)heterostructures: a synergistic experimental and computational investigation - Rondiya, Sachin R.; Karbhal, Indrapal; Jadhav, Chandradip D.; Nasane, Mamta P.; Davies, Thomas E.; Shelke, V. Manjusha; Jadkar, Sandesh R.; Chavan, Padmakar G.; Dzade, Nelson Y. (RSC Advances, 2020)
The unique structural merits of heterostructured nanomaterials including the electronic interaction, interfacial bonding and synergistic effects make them attractive for fabricating highly efficient optoelectronic devices. Herein, we report the synthesis of MnO(2)nanorods and a rGO/MnO(2)nano-heterostructure using low-cost hydrothermal and modified Hummers' methods, respectively. Detailed characterization and confirmation of the structural and morphological properties are doneviaX-ray Diffraction (XRD), Field Emission Scanning Electron Microscopy (FESEM) and Transmission Electron Microscopy (TEM). Compared to the isolated MnO(2)nanorods, the rGO/MnO(2)nano-heterostructure exhibits impressive field emission (FE) performance in terms of the low turn-on field of 1.4 V mu m(-1)for an emission current density of 10 mu A cm(-2)and a high current density of 600 mu A cm(-2)at a relatively very low applied electric field of 3.1 V mu m(-1). The isolated MnO(2)nanorods display a high turn-on field of 7.1 for an emission current density of 10 mu A cm(-2)and a low current density of 221 mu A cm(-2)at an applied field of 8.1 V mu m(-1). Besides the superior FE characteristics of the rGO/MnO(2)nano-heterostructure, the emission current remains quite stable over the continuous 2 h period of measurement. The improvement of the FE characteristics of the rGO/MnO(2)nano-heterostructure can be ascribed to the nanometric features and the lower work function (6.01 and 6.12 eV for the rGO with 8% and 16% oxygen content) compared to the isolated alpha-MnO2(100) surface (phi= 7.22 eV) as predicted from complementary first-principles electronic structure calculations based on density functional theory (DFT) methods. These results suggest that an appropriate coupling of rGO with MnO(2)nanorods would have a synergistic effect of lowering the electronic work function, resulting in a beneficial tuning of the FE characteristics.